Andrychów: Historia wsi, miasta i gminy - Rajman, Jerzy (2024)
ANDRYCHÓW: A HISTORY OF THE VILLAGE, TOWN AND MUNICIPALITYThe municipality of Andrychów straddles River Wieprzówka in the Little Beskids mountain range and the Western Beskidian Foothills. The municipality has approximately 100 km2 of surface area and a population of around 44 thousands. The municipality of Andrychów is home to the city of Andrychów and the villages of Inwałd, Zagórnik, Sułkowice, Łęg, Bolęcina, Brzezinka, Targanice, Rzyki, and Roczyny. Inwałd was established in 1317 as a colony set up by one Sznok, mandated to do so by Wladislaus I, Duke of Oswiecim. Andrychów emerged soon after as a village the name of which stems from its founder, one non-descript Henryk. Both villages were fiefdoms of the knights of the Duchy of Oswiecim, becoming centres of small parishes – the Most Holy Virgin Mary in Inwałd and St. Matthias the Apostle in Andrychów. Once the Duchy of Oswiecim was partitioned in 1445, both villages were in the Duchy of Zatorze. More recent settlements emerged in the second half of the 1500s. All villages in both parishes were already home to a large population of smallholders and landless farmers, which favoured non-agricultural production, a symptom of which was the glassworks in Rzeczki. In the 17th century, the Andrychów Hub was formed, whose founder was a nobleman, Marian Przyłęcki. In 1698, the Hub’s estate became the property of House Schwarzember-Czerny, with the title owned later on by House Ankwicz. The importance of Andrychów as a cluster of weaving mills would grow gradually. By the end of the 18th century, there was a weaving shop in nearly all homes in the village, along with an assortment of bleaching plants, dyeing plants, and horse-powered textile mangles. The drill manufactured in Andrychów became a world-famous commodity, exported by companies set up by the locals. The importance of  Andrychów as a local trading hub was reaffirmed in 1750 with a royal charter to hold fairs in the village, while in 1767, Stanisław Ankwicz was chartered by the Polish king to found a town, the limits of which were established in 1768 to include the village lands. Since the foundation of the town of Andrychów, it was managed by a mayor with a town council. Under the rule of the Austrian Empire after the Partitions, the name Andrychów was understood to include both the township, the rural municipality of villages, and the park lands of the local noble estate.